Ungkapan Bermakna Budaya Masyarakat Nelayan (Suatu Kajian Antropolinguistik) - Lontoh, Irma Maria; Pakasi, Jenny Hilda; Salea-Warouw, Martha (Kajian Linguistik, 2019)
The fishermen community is a community found in North Sulawesi, especially in the coastal area of Sario-Malalayang, Manado. With different cultural backgrounds, ethnicities, this group has its own uniqueness, especially in language. This research succeeded is finding expressions in the fishermen community in the coastal area of Sario-Malalayang. These expressions consist of forms of words, phrases, and clauses in accordance with the lingual forms of theory from Widdowson (1997: 3). The results of the study found a number of lingual forms in affixed words, which had a similar prefix as in the words ba-daseng, ba-kintu, ba-tono, ba-saoh, ba-pake. In addition, the majority of phrases contained in the results of the study are predominantly dominated by noun phrases, such as in the lips phrases of napo, puru loe, coolies, ikang itching, mulu sosoroka, gargantang tubir.This research also succeeded in exploring and discovering cultural meanings. The meanings in the form of words, such as ‘badaseng’, ‘sunga’, then the form of a phrase, like ‘puru loe’, ‘mulu sosoroka’, then sentence expressions in the form of expressions like ‘udang deng katang so kurang sama’, ‘kase wora mar jang talapas’, ‘karja cuma sampe di kuli aer’, etc. The expressions encountered generally contain various cultural meanings, namely advice, satire, ridicule, seduction, warning, insults, and despair. Based on the conclusion, the researcher suggests to the next researcher, to be more comprehensive related to the use of Manado Malay language expression in different background and contexts in order to get a whole description about expressions system of Manado Malay language, especially in the fishermen community in North Sulawesi.Keywords: fishermen community, language and culture